The use of doppler ultrasound in evaluation and follow-up of arteriovenous fistula patients - Kahraman, Nail; Özsin, Kadir Kaan (The European Research Journal, 2018)
Objectives: The aim of the present study was to search the effect of preoperative Doppler ultrasonography (DUS) of the concerning limb on AVF patency for arteriovenous fistula (AVF) to be performed on the patients with end-stage renal disease. Methods: One hundred and three patients were enrolled into the study. The exclusion criteria were previous central catheter procedure, history of thrombophlebitis on the upper limb and previous surgery on the upper limb. Among the remaining patients, those who fulfilled the physical examination criteria were included. The patients were divided into two groups as the control, DUS (-) group and the study group, DUS (+). The patients in the control group were taken into the procedure after a physical examination only. Brescio-Cimino method was preferred for all patients. Function of the AVF was controlled on the procedure day, at day 10, months 1, 3 and 6 as well as year 1 after the procedure. The results in both groups were statistically evaluated. Results: Twenty patients in the DUS (+) group (50% male, mean age: 57.25 ± 13.34 years) and 20 patients in the DUS (-) group (45% male, mean age: 56.10 ± 12.35) were recorded in the study. Cumulative primary patency rates between DUS (+) group and DUS(-) group for 12 months were 95% and 65%, respectively (log-rank, p = 0.022). Conclusion: We believe that the DUS performed before AVF procedure would increase the primary patency rates of AVF created between the most convenient vessels and reduce the procedure failure.